Managing Wildlife in a Changing World - Kideghesho, Jafari R. (IntechOpen, 2021)
The declining trends of wildlife habitats and species populations are obvious consequences of the socio-economic, political, ecological, and technological changes occurring globally. Along with human population growth, there is a growing wave of wildlife diseases, invasive alien species, human-wildlife conflicts, climate change, poaching, infrastructure development, and economic options that are ecologically damaging. These changes have implications on the management of wildlife resources. Managing Wildlife in a Changing World draws experiences from different parts of the world on status, challenges, and efforts of reversing the current negative trends on wildlife habitats and species in the face of these changes. This book is useful for academicians, researchers, policy makers, conservation practitioners, students, and other interested readers.